HUBUNGAN POLA PEMBERIAN MP-ASI DENGAN STATUS GIZI BALITA YANG ADA DI WILAYAH KERJA PUSKESMAS SUKAMULYA KECAMATAN DARUL MAKMUR KABUPATEN NAGAN RAYA - Eldara, Salma Putri; Halimatusa’diyah; Nurlinda, Nova; Rosdeni, Alpa; Aprilia, Lusi (STIKes Mitra Husada Medan, 2026)
Background : Nutritional status is one indicator of a child's health. Nationally, the prevalence of underweight is 19.6%, consisting of 5.7% severe malnutrition and 13.9% moderate malnutrition. In Indonesia, 18 provinces have prevalence rates of underweight and malnutrition above 21.2%, ranging from 33.1% in some areas. Exclusive breastfeeding is one factor that influences nutritional status in toddlers. Providing complementary foods that do not meet standards can lead to nutritional problems in toddlers, such as being underweight or overweight. The Sukamulya Community Health Center (Puskesmas) is the focus of this research because preliminary data shows variations in nutritional status that need to be studied in relation to complementary feeding patterns. The aim of the study : was to determine the relationship between the pattern of providing complementary feeding with the nutritional status of toddlers in the working area of ​​the Sukamulya Health Center, Darul Makmur District, Nagan Raya Regency.Research Methods : This study is an observational analytical study with a cross-sectional approach. This study was conducted in January 2026 in the working area of ​​the Sukamulya Community Health Center, Nagan Raya Regency. The population in this study were all mothers who had toddlers in the working area of ​​the Sukamulya Community Health Center, Nagan Raya Regency, while the number of samples was taken using the Solvin formula, totaling 91 respondents, the sampling technique used the accidental sampling technique.The results of the study : were analyzed using univariate and bivariate analysis and tested using the Chi-Square test. The results of the study after conducting the Chi-Square Test showed that there was a significant relationship between the pattern of providing complementary feeding (the suitability of the type of food and the frequency of giving) with the nutritional status of toddlers (p-value <0.05). The initial time of providing complementary feeding did not show a significant relationship with nutritional status (p-value <0.05). Conclusion:There is a significant relationship between complementary feeding patterns (type and frequency of feeding) and the nutritional status of toddlers in the Sukamulya Community Health Center (Puskesmas) work area. Efforts to improve parental education regarding appropriate complementary feeding are needed to improve toddler nutritional status. Keywords: Complementary feeding; Nutritional Status; Toddlers; Sukamulya ​​ Community Health Center; Nagan Raya Regency.